Strengthening school literacy programs with support from library collection development - Ghina Afiifah Safiinatunnajah; Dina Siti Logayah (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Literacy is a skill that everyone must own. This literacy skill includes processing, understanding, and interpreting information about matters in specific fields. The information was obtained as support and survival. The urgency of cultivating literacy is becoming an increasingly important topic to be intensified at this time. Various ways are done so the community can fully master that literacy. One of them is by empowering the school library. Empowerment of the school library in this activity focuses on collection development. The development of school library collections is an activity schools must carry out to support student learning facilities. However, several schools still need to implement library collection development. One of them is the UPI Literacy Thematic KKN activity, namely at the Tahfidzul Qur'an Al-Ishlah Putri Islamic Boarding School, which is located in Bogor Regency. Based on these problems, the author seeks to design a community service program in the Tahfidzul Qur'an Al-Ishlah Putri Islamic Boarding School library to support the school's literacy program. The service method implemented is strengthening the school literacy program with support for developing library collections. The results of this program are a concern and the starting gate for the sustainability of literacy activities at the Tahfidzul Qur'an Al-Ishlah Putri Islamic Boarding School.   Abstrak Literasi merupakan keterampilan yang harus dimiliki oleh semua orang. Keterampilan literasi ini mencakup mengolah, memahami, serta memaknai informasi mengenai hal-hal di bidang tertentu. Informasi tersebut didapatkannya sebagai penunjang serta kecakapan hidup. Urgensi pembudayaan literasi menjadi topik yang semakin penting untuk digencarkan saat ini. Berbagai cara dilakukan agar literasi dapat sepenuhnya dikuasai oleh masyarakat. Salah satunya dengan pemberdayaan perpustakaan sekolah. Pemberdayaan perpustakaan sekolah pada kegiatan ini berfokus pada pengembangan koleksi. Pengembangan koleksi perpustakaan sekolah merupakan kegiatan yang wajib dilakukan oleh sekolah untuk menunjang sarana belajar siswa. Namun, terdapat beberapa sekolah yang belum melaksanakan pengembangan koleksi perpustakaan. Salah satunya adalah tempat kegiatan KKN Tematik Literasi UPI yaitu di Pesantren Tahfidzul Qur’an Al-Ishlah Putri yang beralamatkan di Kabupaten Bogor. Berdasarkan permasalahan tersebut, penulis berupaya merancang program pengabdian di perpustakaan Pesantren Tahfidzul Qur’an Al-Ishlah Putri dapat mendukung program literasi sekolah. Metode pengabdian yang dilaksanakan yaitu penguatan program literasi sekolah dengan dukungan pengembangan koleksi perpustakaan. Hasil program ini menjadi perhatian dan gerbang awal bagi keberlangsungan kegiatan literasi di Pesantren  Tahfidzul Qur’an Al-Ishlah Putri. Kata Kunci: Pengembangan koleksi; penguatan literasi sekolah; perpustakaan sekolah; perpustakaan pesantren